2000
DOI: 10.1359/jbmr.2000.15.7.1321
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Induces Expression of Receptor Activator of Nuclear Factor–κB Ligand/Osteoprotegrin Ligand on Pre-B Cells: Implications for Accelerated Osteoclastogenesis in Estrogen Deficiency

Abstract: Estrogen deficiency causes bone loss as a result of accelerated osteoclastic bone resorption. It also has been reported that estrogen deficiency is associated with an increase in the number of pre-B cells in mouse bone marrow. The present study was undertaken to clarify the role of altered B lymphopoiesis and of the receptor activator of nuclear factor-B ligand (RANKL), a key molecule in osteoclastogenesis, in the bone loss associated with estrogen deficiency. In the presence of prostaglandin E 2 (PGE 2 ), the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
94
2
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(100 citation statements)
references
References 36 publications
3
94
2
1
Order By: Relevance
“…One such mechanism involves RANKL expression by lymphocytes. Specifically, ovariectomy in mice increases the number of RANKL-expressing B lymphocytes in the bone marrow (16). Consistent with this, orchidectomy of rats increases soluble RANKL (sRANKL) levels in the bone marrow (17,18).…”
mentioning
confidence: 65%
See 1 more Smart Citation
“…One such mechanism involves RANKL expression by lymphocytes. Specifically, ovariectomy in mice increases the number of RANKL-expressing B lymphocytes in the bone marrow (16). Consistent with this, orchidectomy of rats increases soluble RANKL (sRANKL) levels in the bone marrow (17,18).…”
mentioning
confidence: 65%
“…In vitro studies have demonstrated that B cells at several stages of differentiation, from early precursors to plasma cells, can support osteoclast formation (16,(35)(36)(37)(38)(39). Nonetheless, Weitzmann and colleagues have shown that ovariectomy led to similar amounts of bone loss in mice lacking mature B cells compared with control littermates, suggesting that mature B cells are not required for the bone loss caused by estrogen deficiency (40).…”
Section: Discussionmentioning
confidence: 99%
“…48 The number of RANKL-expressing B lymphocytes in the bone marrow increases after OVX. 49 Recently, Onal et al 50 demonstrated that RANKL produced by B cells and not by T cells have a role in OVX-induced bone loss in mice. This paper disagrees with previous reports showing a fundamental role of RANKL produced by T cells in OVX-induced bone loss.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%
“…(6)(7)(8) Most previous studies have focused on the total amount of RANK ligand (RANKL) expressed in whole osteoblastic cells, including studies focused on transcriptional regulation of RANKL. (9)(10)(11) However, only RANKL molecules expressed at the cell surface actually can bind to RANK, which is located at the cell surface of osteoclast precursor cells. (12)(13)(14) Therefore, the quantity of RANKL on the osteoblastic cell surface could determine the magnitude of the signal input and the degree of osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%